Analisis Seleksi dan Gradasi Materi Buku Teks Al-Arabiyyah baina Yadaik - Syarifah Syarifah (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2020)
In achieving learning objectives, one of very important component is the right textbook. The use of appropriate textbooks greatly affects the success of learning. Therefore, the analysis of a textbook, in this case, a textbook for Arabic learning, is very important to do. The purpose of this study is to describe the selection and gradation of material in the Arabic textbook Al-Arabiyyah baina Yadaik. The type of research used in this study is library research, using the content analysis method. The object of this research is Arabic textbooks that are widely used in the world of education, especially universities, namely: Kitab Al-Arabiyyah baina Yadaik volumes I and II. Based on this this study it can be concluded that the material selection in the Al-Arabiyyah baina Yadaik textbook has fulfilled the principles of material selection: frequency, range, availability, coverage, and learnability. The gradation of material in the textbook Al-Arabiyyah baina Yadaik, generally, has fulfilled the principles of gradation. If viewed in terms of type, the book Al-Arabiyyah baina Yadaik uses a rotating gradation pattern, whereas if it is based on language categories, the textbooks uses a national-functional gradation pattern.